Titanium dioxide nanotube rich in oxygen vacancy defects and preparation method thereof

By introducing oxygen vacancy defects into the TiO2 nanotube array and using the titanium sheet bending stress and annealing heat treatment method, the application of TiO2 nanotube array in the field of photoelectro-catalytics is solved by the problem that the high band gap width and high electron hole recombination rate of the application of TiO2 nanotube array in the field of photoelectro-catalytics, and the effect of improving the utilization rate of visible light and photoelectro-catalytic performance is achieved.

CN116139843BActive Publication Date: 2025-04-11TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211541329.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2025-04-11
Estimated Expiration
2042-12-02

AI Technical Summary

Technical Problem

The application of existing TiO2 nanotube arrays in the field of photoelectrocatalysis is limited by their high band gap width and high electron hole recombination rate, resulting in low utilization of visible light and low catalytic activity.

Method used

By bending the titanium sheet to form a ring, introducing bending stress during the anodization process, and then releasing the stress by annealing heat treatment, titanium dioxide nanotubes rich in oxygen vacancy defects are formed.

Benefits of technology

This method effectively reduces the bandwidth of TiO2, improves the utilization rate of visible light, enhances the separation efficiency of photogenerated electron holes, and significantly improves the photoelectrocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116139843B_ABST
    Figure CN116139843B_ABST
Patent Text Reader

Abstract

The present invention discloses a titanium dioxide nanotube rich in oxygen vacancy defects and a preparation method thereof. The Ti sheet is bent so that extrusion stress is formed during the vertical growth of TNAs on the tube wall. The bent TNAs are annealed to release the stress, resulting in the formation of lattice defects (oxygen vacancies) of the TNAs. The present invention simply regulates the oxygen vacancies of the titanium dioxide nanotube array, and more oxygen atom vacancies can serve as traps for electrons and holes in the photocatalytic reaction process, promote the separation of photogenerated electron-hole pairs, capture more electrons, and improve the photocatalytic performance of the TNAs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a titanium dioxide nanotube, in particular to a titanium dioxide nanotube rich in oxygen vacancy defects and a preparation method thereof, belonging to the technical field of nano functional material processing. Background Art

[0002] TiO2 has attracted much attention due to its high photoelectrocatalytic (PEC) activity, chemical stability, non-toxicity and relatively low price. Due to the large internal surface area, their unique structural characteristics and crystal properties make them an effective pathway for interfacial vector charge transfer. Among the numerous TiO2 nanomaterials, TiO2 nanotube arrays (TNAs) have been shown to be very effective photoelectrocatalytic photoanodes due to their high-depth pore structure and large specific surface area, and have great potential applications in sensing, fuel cells and water photolysis.

[0003] However, due to the high bandgap of TiO2 (3.0eV-3.2eV), it can only absorb energy in the near-ultraviolet region of visible light, and has a low utilization rate of visible light. In addition, the high recombination rate of electrons and holes leads to low catalytic activity. These two points greatly limit the application of TNAs as photoanode materials in the field of photoelectrocatalysis. It has been proven that by introducing defects (Ti 3+ / V o ) can effectively solve the above two defects. That is, the defect states formed are all in the lower conduction band to form defect energy levels, reducing the band gap width of TiO2 and improving its utilization rate of visible light. The generated Ti 3+ / V o It can serve as a capture center for photogenerated electrons and holes, increasing the efficiency of carrier separation. o It is also the active center of the catalytic reaction, which greatly improves the reactivity of TNAs.

[0004] At present, most of the methods for generating defective TNAs are to introduce them through annealing reduction reaction with reducing substances such as H2, Mg powder, and NaBH4. The substances involved in these methods inevitably have certain safety hazards. Therefore, it is urgent to find a safe and reliable method to introduce defects in TNAs. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a titanium dioxide nanotube rich in oxygen vacancy defects and a preparation method thereof.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing titanium dioxide nanotubes rich in oxygen vacancy defects, the specific steps are as follows:

[0008] (1) First, the titanium sheet is cut into a rectangular shape and bent until the ends are connected to form a ring to obtain a bent titanium sheet;

[0009] (2) Then, the bent titanium sheet is used as an anode, the platinum sheet is used as a cathode, and an ethylene glycol aqueous solution containing ammonium fluoride is used as an electrolyte, and an anodic oxidation reaction is performed, followed by annealing and heat treatment, thereby obtaining the titanium dioxide nanotubes.

[0010] Preferably, in step (1), the thickness of the titanium sheet is 0.1 mm, the width is 2 cm, and the diameter of the ring is 1 to 6 cm.

[0011] Preferably, in step (1), the titanium sheet is cleaned and dried after cutting, and the specific method of the cleaning treatment is: ultrasonic cleaning with acetone, anhydrous ethanol and deionized water for 10 to 30 minutes in sequence to remove surface oil and organic matter.

[0012] Further preferably, the process conditions for ultrasonic cleaning are: frequency 50 kHz, power 10-50 W.

[0013] Further preferably, the drying process conditions are: drying at 10-80° C. for 1-3 hours.

[0014] Preferably, in step (2), the electrolyte is obtained by dissolving ammonium fluoride in an ethylene glycol aqueous solution so that the mass concentration of ammonium fluoride is 1-5%, wherein the ethylene glycol aqueous solution is obtained by mixing ethylene glycol and water in a volume ratio of 0.1-10:99.9-90.

[0015] Preferably, in step (2), the process conditions of the anodization reaction are: a DC voltage of 20 to 80 V, and a reaction time of 20 minutes to 4 hours.

[0016] Preferably, in step (2), the process conditions of the degradation heat treatment are: 300-800° C. for 1-6 hours.

[0017] A titanium dioxide nanotube rich in oxygen vacancy defects is obtained by the preparation method.

[0018] The above-mentioned titanium dioxide nanotube rich in oxygen vacancy defects is used as a photoanode material for photoelectrocatalysis.

[0019] Beneficial effects of the present invention:

[0020] In the process of forming TNAs by the conventional anodizing method, the Ti sheet is bent so that the TNAs form extrusion stress during the vertical growth process on the tube wall. The bent TNAs are annealed to release the stress, resulting in the formation of lattice defects (oxygen vacancies) of the TNAs. The present invention simply regulates the oxygen vacancies of the titanium oxide nanotube array, and more oxygen atom vacancies can serve as traps for electrons and holes in the photocatalytic reaction process, promote the separation of photogenerated electron-hole pairs, capture more electrons, and improve the photocatalytic performance of the TNAs.

[0021] Compared with the traditional methods for preparing defective titanium TNAs, such as high-temperature reduction of Mg and Al powders, H2 atmosphere treatment, NaBH4 reduction method, etc., the method of the present invention is safer and more convenient, and does not change the structure and composition of the tube. The synthesis process is clean and pollution-free, and the synthetic raw materials are non-toxic and pollution-free, and are easy to recycle.

[0022] The advantages of the present invention are specifically analyzed as follows:

[0023] 1. The method of generating oxygen vacancies by inducing bending stress to generate TNAs is more convenient and quick. It is only necessary to bend and oxidize the Ti sheet substrate during the anodizing process, and then put the generated TNAs into a muffle furnace for annealing. The traditional method uses H2, Mg powder, NaBH4 and other reducing substances for annealing reduction reaction, and the raw materials used are generally flammable and explosive. The present invention is safer, more reliable, clean and pollution-free.

[0024] 2. The bending stress of TNAs can be changed by changing the thickness of the Ti sheet and the bending diameter, and the concentration of Vo can be regulated by changing the stress accordingly. This enables the controllable preparation of defective TNAs. The regulation method is safe and stable.

[0025] 3. In addition to the controllable defect concentration of TNAs prepared by bending stress, the bending stress of Ti and TNAs is released from the interface between the two to the nozzle during the annealing process. The bending stress of the Ti sheet is released from bottom to top during the annealing process, that is, from the interface between TNAs and Ti sheets to the nozzle. The defects formed are also arranged from top to bottom, and the defect distribution is more uniform. However, defective TNAs prepared using H2, Mg powder, etc. may not be in complete contact with the material surface, resulting in most defects concentrated on the nozzle surface.

[0026] 4. TNAs prepared by bending stress can effectively improve their photoelectrocatalytic performance. Compared with ordinary TNAs, the photocurrent is increased by about 4-8 times (the photocurrent density of pure TNAs is about 0.3mA / cm 2 The highest TNAs photocurrent for bending defects is about 2.5 mA / cm 2 ). BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The figure is a flow chart for the preparation of titanium dioxide nanotubes, wherein a is a flat titanium sheet without bending, and b is a bent titanium sheet.

[0028] Figure 2 These are SEM images of TNAs prepared in Example 1 of the present invention, wherein a is a titanium flat plate without bending, b is a ring with a diameter of 10 mm, c is a ring with a diameter of 15 mm, d is a ring with a diameter of 20 mm, and eh are partial enlarged views of ad, respectively.

[0029] Figure 3 The bending stress characterization and vacancy concentration EPR characterization results of the Ti sheet in Example 1, wherein a is the fitting curve of three groups of bending stresses, and b is the three groups of bending stress values ​​calculated by a.

[0030] Figure 4 This is the ESR result of the sample in Example 1.

[0031] Figure 5 This is the current-time curve of Example 1.

[0032] Figure 6 The results of stress regulation by changing the thickness of the plate at the same bending radius, where a is the stress result generated by bending into a D = 15mm ring with different thicknesses, and b is the ESR result of TNAs with different thicknesses.

[0033] Figure 7 This is the current-time curve of Example 2.

[0034] Figure 8 These are the photocurrent density curves of the three samples in Example 2.

[0035] Fig. 9 This is a characterization of the chemical environment of the O element on the surface and bottom of the three samples in Example 3. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with embodiments. It should be noted that the following description is only for explaining the present invention and does not limit its contents.

[0037] Embodiment 1:

[0038] like Figure 1 The preparation of titanium dioxide nanotubes is shown in the figure, wherein a is a titanium sheet without bending, and b is a titanium sheet bending, that is, the method of the present invention for regulating oxygen vacancies in titanium dioxide nanotube arrays by using bending stress of a Ti sheet, comprises the following steps:

[0039] S1, a 0.1 mm thick Ti sheet was ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water at a frequency of 50 kHz and a power of 10 W for 10 minutes, dried at 10°C for 3 hours, and then bent into rings with diameters of 10 mm, 30 mm, and 60 mm. A 0.1 mm*10 mm*30 mm Ti sheet was used as the control group.

[0040] S2, anodizing to prepare TNAs.

[0041] S3, drying the prepared TNAS at 10°C for 3 hours, and then placing it in a muffle furnace for heat treatment at 300°C for 6 hours.

[0042] S4, performing a photocurrent density test on the above samples to evaluate their photoelectrocatalytic activity.

[0043] Specifically, step S2 includes: using a cleaned titanium sheet as an anode and a platinum sheet as a cathode, applying a DC voltage of 20 V in an electrolyte (ammonium fluoride is dissolved in an ethylene glycol aqueous solution so that the mass concentration of ammonium fluoride is 1%, wherein the ethylene glycol aqueous solution is obtained by mixing ethylene glycol and water in a volume ratio of 0.1:99.9) for 4 hours to obtain a titanium dioxide nanotube array.

[0044] Step S4 includes: using the Pt sheet as the counter electrode, the Ti sheet as the working electrode, and the saturated calomel as the reference electrode, the three-electrode system applies a bias voltage of 0.5938V to test the photocurrent density. The test electrolyte is a 0.5 mol / L sodium sulfate aqueous solution, and the light intensity is 500 mW / cm 2 .

[0045] Figure 2 The SEM images of TNAs prepared in Example 1, wherein a is a titanium flat plate without bending, b is a ring with a diameter of 10 mm, c is a ring with a diameter of 15 mm, d is a ring with a diameter of 20 mm, and eh are partial enlarged images of a and b, respectively. It can be seen from the figure that the bending of the Ti sheet does not change the pore structure of the TNAs, and the extremely large specific surface area of ​​the pore structure is still maintained.

[0046] Figure 3 The bending stress characterization and vacancy concentration EPR characterization results of the Ti sheet in Example 1, wherein a is the fitting curve of three groups of bending stresses, and b is the three groups of bending stress values ​​calculated by a.

[0047] Figure 4 The ESR results of the sample in Example 1. The characteristic signal of oxygen vacancies in TNAs represented by g = 2.002, its concentration is positively correlated with its signal intensity. Figure 3 and Figure 4It can be seen that as the bending radius decreases, the bending stress gradually increases, and the corresponding oxygen vacancy concentration of the annealed TNAs also gradually increases.

[0048] Figure 5 The current-time curve of Example 1 shows the highest photocurrent density (2.4 mA / cm 2 ) compared to the photocurrent density of pure TNAs (0.3 mA / cm 2 ) increased by about 8 times.

[0049] Example 2

[0050] In this embodiment, Ti sheets of different thicknesses (thickness = 0.05 mm, 0.10 mm, 0.15 mm) were bent into a ring with a diameter of 15 mm and a flat Ti sheet were anodized and then subjected to retreat treatment for comparison.

[0051] S1, Ti sheets with thickness of 0.05mm, 0.10mm and 0.15mm were ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 30 minutes at a frequency of 50kHz and a power of 30W, dried at 80℃ for 1 hour, and then bent into a ring with a diameter of 15mm. A Ti sheet flat plate with the same area was used as the control group (0.1mm*20mm*47.1mm).

[0052] S2, preparation of TNAs by anodization.

[0053] S3, drying the prepared TNAS at 50°C for 2 hours, and then placing it in a muffle furnace for heat treatment at 450°C for 3 hours.

[0054] S4, the photoelectrocatalytic performance of the above samples was evaluated, and the three groups of samples were characterized by XRD and EPR to evaluate the relationship between their vacancy concentration and stress.

[0055] Specifically, step S2 includes: using a cleaned titanium sheet as an anode and a platinum sheet as a cathode, applying a DC voltage of 50 V for oxidation time of 1 h in an electrolyte (ammonium fluoride is dissolved in an ethylene glycol aqueous solution so that the mass concentration of ammonium fluoride is 3%, wherein the ethylene glycol aqueous solution is obtained by mixing ethylene glycol and water in a volume ratio of 2:98) to obtain a titanium dioxide nanotube array.

[0056] Step S4 includes: using the Pt sheet as the counter electrode, the Ti sheet as the working electrode, and the saturated calomel as the reference electrode, the three-electrode system applies a bias voltage of 0.5938V to test the photocurrent density. The test electrolyte is 0.5 mol / L anhydrous sodium sulfate, and the light intensity is 500 mW / cm 2 .

[0057] Figure 6The results of stress regulation by changing the thickness of the plate at the same bending radius. a is the stress result generated by bending into a D=15mm ring with different thicknesses. b is the ESR result of TNAs with different thicknesses. From a and b, it can be seen that the thickness can also effectively regulate the magnitude of lattice stress, thereby controlling the concentration of vacancies.

[0058] Figure 7 The current-time curve of Example 2 shows that the photocurrent density of TNAs increases gradually with the increase of bending stress, and the maximum photocurrent density is (3.0 mA / cm 2 ) is about 10 times higher than that of pure tube TNAs.

[0059] Therefore, based on Examples 1 and 2, it can be found that the bending stress can be effectively controlled by changing the physical dimensions of the Ti sheet, so that defective TNAs can be prepared simply, efficiently and controllably by releasing the stress during the annealing process.

[0060] Figure 8 The photocurrent density curves of the three samples in Example 2 are shown in Figure 2. The photocurrent density of the TNAs with a bend of 15 mm (2.4 mA / cm 2 ) is higher than the photocurrent density of hydrogen treatment (1.25mA / cm 2 ) is about 1.92 times higher. This fully demonstrates the superiority of the present invention.

[0061] Example 3

[0062] In this embodiment, a Ti sheet with a bending diameter of 15 mm, a flat Ti sheet, and a Ti sheet treated with hydrogen after flat oxidation are compared.

[0063] S1, a Ti sheet with a thickness of 0.1 mm was ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water at a frequency of 50 kHz and a power of 50 W for 20 minutes, dried at 60 ° C for 2 hours, and then bent into a ring with a diameter of 15 mm. A Ti sheet with the same area was used as the control group (0.1 mm*20 mm*47.1 mm).

[0064] S2, preparation of TNAs by anodization.

[0065] S3, drying the prepared TNAS at 80°C for 1 hour, and then placing it in a muffle furnace for heat treatment at 800°C for 1 hour.

[0066] S4, the photoelectrocatalytic performance of the above samples was evaluated, and the surface and bottom of the three groups of samples were characterized by XPS to evaluate their vacancy concentration.

[0067] Specifically, step S2 includes: using a cleaned titanium sheet as an anode and a platinum sheet as a cathode, applying a DC voltage of 80 V for an oxidation time of 20 minutes in an electrolyte (ammonium fluoride is dissolved in an ethylene glycol aqueous solution so that the mass concentration of ammonium fluoride is 5%, wherein the ethylene glycol aqueous solution is obtained by mixing ethylene glycol and water in a volume ratio of 10:90) to obtain a titanium dioxide nanotube array.

[0068] Step S4 includes: using the Pt sheet as the counter electrode, the Ti sheet as the working electrode, and the saturated calomel as the reference electrode, the three-electrode system applies a bias voltage of 0.5938V to test the photocurrent density. The test electrolyte is 0.5 mol / L anhydrous sodium sulfate, and the light intensity is 500 mW / cm 2 The TNAs were peeled off from the Ti substrate by repeatedly bending the Ti sheet until the oxidized film was completely peeled off.

[0069] Fig. 9 The chemical environment of the O element on the surface and bottom of the three samples in Example 3 is characterized. It can be found that the TNAs after bending stress annealing have obvious XPS signal peaks of O vacancies at the bottom and surface at a binding energy of 532.5eV. The ordinary flat TNAs treated with hydrogen only have signal peaks of O vacancies on the surface, but the chemical environment of O at the bottom does not show signal peaks of O vacancies, which indicates that the vacancies induced by the H2 treatment only act on the surface of the catalyst, and the bottom still maintains a complete crystal structure. The normally annealed TNAs have no obvious XPS signals of O vacancies on either the surface or the bottom. And the area of ​​the XPS signal represents the relative content. It can be seen that whether it is the vacancy concentration on the surface or the bottom, the stress-induced vacancy concentration is much greater than the vacancy concentration treated with H. Therefore, whether it is from the distribution of vacancies or the concentration, the superiority of TNAs with stress-induced vacancies is far higher than that of defective TNAs treated by conventional means.

[0070] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.

Claims

1. A method for preparing titanium dioxide nanotubes rich in oxygen vacancy defects, characterized in that: The specific steps are as follows: (1) First, cut the titanium sheet into a rectangular shape and bend it until the ends are connected to form a ring to obtain a bent titanium sheet; (2) Then, the bent titanium sheet is used as an anode, the platinum sheet is used as a cathode, an ethylene glycol aqueous solution containing ammonium fluoride is used as an electrolyte, an anodic oxidation reaction is performed, and an annealing heat treatment is performed to obtain the titanium dioxide nanotubes; In step (2), the electrolyte is prepared by dissolving ammonium fluoride in an ethylene glycol aqueous solution so that the mass concentration of the ammonium fluoride is 1-5%, wherein the ethylene glycol aqueous solution is prepared by mixing ethylene glycol and water in a volume ratio of 0.1-10:99.9-90; The process conditions of the anodic oxidation reaction are: a DC voltage of 20 to 80 V, and a reaction time of 20 minutes to 4 hours; The process conditions of annealing heat treatment are: 300-800°C for 1-6 hours.

2. The preparation method according to claim 1, characterized in that: In step (1), the thickness of the titanium sheet is 0.1 mm, the width is 2 cm, and the diameter of the ring is 1 to 6 cm.

3. The preparation method according to claim 1, characterized in that: In step (1), the titanium sheet is cleaned and dried after cutting. The specific method of the cleaning process is: ultrasonic cleaning with acetone, anhydrous ethanol and deionized water for 10 to 30 minutes in sequence.

4. The preparation method according to claim 3, characterized in that: The process conditions for ultrasonic cleaning are: frequency 50kHz, power 10~50W.

5. The preparation method according to claim 3, characterized in that: The drying process conditions are: drying at 10-80°C for 1-3 hours.

6. A titanium dioxide nanotube rich in oxygen vacancy defects, characterized in that: The invention is obtained by the preparation method according to any one of claims 1 to 5.

7. Use of the titanium dioxide nanotube rich in oxygen vacancy defects as claimed in claim 6 as a photoanode material for photoelectrocatalysis.

Citation Information

Patent Citations

  • Manganese-doped titanium dioxide nanotube array membrane, gas-sensitive element and preparation method for gas-sensitive element

    CN107268061A